KONSEP DAN PRAKTEK MEMUJI DAN MENYEMBAH TUHAN SECARA BIBLIKA BERDASARKAN KITAB MAZMUR: HALLELUYAH - Antonius Hutapea (STT IKSM SANTOSA ASIH, 2025)
Abstract The phrase Hallelujah is often understood as merely praising God. In fact, the meaning of Hallelujah is not just saying praise God but how to praise and worship God. In the Psalms, the word Hallelujah is often repeated as a repetition at the beginning and end of the passage, such as Psalms 106, 113, 117, 146 to Psalm 150, which we call inclusio (repetition) to remind us of the importance of this Hallelujah word. The research method used is qualitative poetic reflective. Exegesis of the Hebrew text of the word hallelujah, biblically. This article will describe the main purpose of the Psalms is to arouse praise to God. The Psalms, which consist of 150 chapters, almost half (73 chapters) written by David, want to teach us not only to say praise God, praise God, or hallelujah but to have a concept and practice of praising and worshiping God. Abstrak Frasa kata Halleluyah sering dipahami hanya sebatas puji Tuhan semata. Padahal arti Halleluyah bukan sekedar berkata puji Tuhan tetapi bagaimana sikap memuji dan menyembah Tuhan. Dalam Mazmur kata Halleluyah sering diulang sebagai suatu repitisi diawal serta akhir perikop, seperti Mazmur 106, 113, 117, 146 hingga Mazmur 150, yang kita sebut sebagai inklusio (pengulangan) untuk ”mengingatkan kita pentingnya kata Halleluyah ini.” Metode penelitian yang digunakan bersifat kualitatif puitis reflektif. Mengeksegese teks Ibrani kata halleluyah, secara biblikal. Artikel ini akan menguraikan tujuan utama Mazmur adalah untuk membangkitkan pujian kepada Allah. Mazmur yang terdiri dari 150 pasal itu, hampir setengahnya (73 pasal) ditulis oleh Daud, ingin mengajarkan kita bukan hanya berkata terpuji Tuhan, puji Tuhan, atau halleluyah namun memiliki konsep dan praktek hidup memuji dan menyembah Allah.